DESIGN & VALIDATION of SOLAR-POWERED STREET LIGHTING PROTOTYPE for AIRPORT DROP-OFF AREA - Muhammad Daru Balvero; Asep Muhamad Soleh (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2026)
The drop-off area of Husein Sastranegara International Airport Bandung lacks street lighting, posing safety risks to passengers and vehicles. This study designed and validated a solar-powered lighting prototype for that area using a quantitative Research and Development (R&D) approach following the Borg & Gall model. Six stages were implemented: problem identification, data collection, product design, design validation, design revision, and product testing. Based on SNI 7391:2008 and PM 27/2018 requirements, a 1:10 scale prototype was constructed comprising a 10 Wp solar cell, 3 W LED lamp, 12 V/5 Ah battery, and Solar Charge Controller. Testing confirmed a solar cell output voltage of 19.30 V at peak irradiance (13:00 WIB, 32°C). Expert validation by three validators yielded an overall score of 86.5% (Very Good for device function; Good for device quality), confirming prototype feasibility for full-scale airport implementation.